Analisis Kedudukan dan Status Hukum Ketetapan MPR RI Berdasarkan Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan - Titik Triwulan Tutik (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research discusses: First, the juridical ratio of the position of People’s Consultative Assembly’s adjudication which re-enters the regulations of law hierarchy. Second, the position and legal status of the People’s Consultative Assembly’s adjudication based on Law Number 12 of 2011 on the Formulation of Regulations of Law compared with the position and legal status of the previous People’s Consultative Assembly’s adjudications. The research method used in this research was normative-juridical method. The approach used was historical and statute approaches. The research finding shows that: First, the position of People’s Consultative Assembly’s adjudication in the regulations of law hierarchy is condition sine quanon. Second, the legal status of the People’s Consultative Assembly’s adjudication based on Law Number 12 of 2011 is different from the People’s Consultative Assembly’s adjudications prior to the amendment of Constitution 1945 of the Republic of Indonesia. This is in regards with the fact that the People’s Consultative Assembly after the amendment of Constitution 1945 has the position as state high institution.